Solution structure of a pentachromium(ii) single molecule magnet from DFT calculations, isotopic labelling and multinuclear NMR spectroscopy. Issue 2 (14th December 2017) - Dirvanauskas, Aivaras; Galavotti, Rita; Lunghi, Alessandro; Nicolini, Alessio; Roncaglia, Fabrizio; Totti, Federico; Cornia, Andrea
Abstract : Solution NMR spectroscopy on isotopically-labelled samples of [Cr5 (tpda)4 Cl2 ] unveils a D 4 symmetric molecule, implying fast shuttling between the two unsymmetric ground configurations over NMR timescale. Abstract : The structure of pentachromium(ii ) extended metal atom chain [Cr5 (tpda)4 Cl2 ] (2 ), which behaves as a single molecule magnet at low temperature, was investigated by Density Functional Theory (DFT) calculations and spectroscopic studies without the constraints of a crystal lattice (H2 tpda = N 2, N 6 -bis(pyridin-2-yl)pyridine-2, 6-diamine). DFT studies both in the gas phase and including CH2 Cl2 solvent effects indicate that an unsymmetric structure ( C 4 point group), with pairs of formally quadruply-bonded metal ions and one terminal metal center, is slightly more stable (2.9 and 3.9 kcal mol −1 ) than a symmetric structure ( D 4 point group). Isotopically-labelled samples (2 - d 8 and2 - d 16 ) have then been prepared to aid in molecular symmetry determination by combined 1 H and 2 H NMR studies in dichloromethane solution. The spectra are strongly suggestive of a symmetric ( D 4 ) framework, indicating fast shuttling between the two unsymmetric forms over the timescale of NMR experiments. Procedures for a high-yield Pd-free synthesis of H2 tpda and for site-selective post-synthetic H/D exchange of aromatic H2 tpda hydrogens are also reported.